Ground observations for mapping surface features from remote sensing images - (:unkn) unknown (My University, 1995)
In west Africa Orstom experiments proved the strong influence of surface features on runoff properties of soils. High resolution remote sensing images give information on surface feature throught vegetation, soils and suoperficial organisation. Processing the images needs specific ground data in order to define the principal indicators of surface features. This paper presents the organisation of ground observations.
Keywords: African Research